2012
DOI: 10.1128/jvi.06103-11
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Mouse-Adapted Enterovirus 71 (EV71) Strain Exhibits Neurotropism, Causing Neurological Manifestations in a Novel Mouse Model of EV71 Infection

Abstract: Enterovirus 71 (EV71) is a neurotropic pathogen that has been consistently associated with the severe neurological forms of hand, foot, and mouth disease. The lack of a relevant animal model has hampered our understanding of EV71 pathogenesis, in particular the route and mode of viral dissemination. It has also hindered the development of effective prophylactic and therapeutic approaches, making EV71 one of the most pressing public health concerns in Southeast Asia. Here we report a novel mouse model of EV71 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
174
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(190 citation statements)
references
References 40 publications
16
174
0
Order By: Relevance
“…8A and B). The results indicated that RG/B4 accumulated in the hind limb muscle and brain throughout the whole experiment; the viral titer and RNA copy number reached the highest levels before the death of infected mice, similarly to a previous description of wild-type B4 infection in AG129 mice (30). In contrast, all high-replication-fidelity variants showed lower viral titers and RNA copy numbers in the hind limb muscle and brain than RG/B4 at each time point.…”
Section: Generation Of Ribavirin-resistant Ev71-b5 Variantssupporting
confidence: 86%
See 3 more Smart Citations
“…8A and B). The results indicated that RG/B4 accumulated in the hind limb muscle and brain throughout the whole experiment; the viral titer and RNA copy number reached the highest levels before the death of infected mice, similarly to a previous description of wild-type B4 infection in AG129 mice (30). In contrast, all high-replication-fidelity variants showed lower viral titers and RNA copy numbers in the hind limb muscle and brain than RG/B4 at each time point.…”
Section: Generation Of Ribavirin-resistant Ev71-b5 Variantssupporting
confidence: 86%
“…Young suckling AG129 mice showed neurological symptoms and even died with wild-type EV71-B4 infection because AG129 mice lack a functional interferon system and support both the spread from the primary infection site and the persistence of EV71 (30). As IFNs play an important role in the antiviral defense against EV71 infection, the LD 50 differences between the parental RG/B4 and its high-fidelity variants described in AG129 mice might even be widened in an immunocompetent host, where fewer mutations in the population of high-fidelity variants might result in a lower likelihood of mutations capable of circumventing established innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EV71, together with coxsackievirus A16 (CVA16) infections are generally associated with hand, foot and mouth disease (HFMD), but EV71 infection occasionally progress to severe neurological disease, including aseptic meningitis, poliomyelitis-like paralysis, and possibly fatal encephalitis in neonates, especially brain stem encephalitis associated with pulmonary edema and cardiac insufficiency which are the primary manifestations in patients with neurologic involvement [11,12]. Numerous animal models have been developed to study the pathogenesis of EV71 infection using the mouse-adapted strain of EV71 in innate immunodeficient mice [13][14][15]. The EV71 BrCr strain was demonstrated to induce neurological manifestation of tremor, ataxia, and brain edema in cynomolgus monkeys [16].…”
Section: Introductionmentioning
confidence: 99%